Pengalaman Mahasiswa dalam Mengikuti Tren Tiktok: Kajian Tentang Konformitas Sosial: Penelitian - Nova Lisye Sinaulan; Alfira Dareho; Chevalir Runtu; Gelegar Runtuwene; Videl Loway (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to explore how students perceive and respond to viral trends on TikTok, as well as to examine how pressure to conform to social norms influences their behaviour when using this social media platform. Through a descriptive qualitative approach involving in-depth interviews with three psychology students, this study reveals that participation in TikTok trends is driven by strong influence from social circles and various personal reasons. The three participants demonstrated diverse forms of conformity, ranging from conformity based on social norms, compromise, to information obtained. The findings highlight that while TikTok serves as a platform for self-expression and entertainment, it also functions as a social environment with expectations for conforming to group standards. The conclusion of this study emphasises that social media plays a significant role in shaping the digital behaviour of today’s youth, but individual responses to social pressure are greatly influenced by personal traits and the values they hold